Bacteriological profile and sensitivity pattern of neonatal sepsis (Northern International Medical College Journal, 2017)
Introduction : Neonatal sepsis remains an important cause of neonatal morbidity and mortality in NICU setup and a major challenge for the neonatologists. The prevalent organisms and their antibiotic resistance patterns evolve with time and with the usage of antimicrobials.Aims and Objectives : To analyze the bacteriological profile and antibiotic resistance patterns of proven neonatal sepsis cases in Dhaka Shishu Hospital.Materials and Methods : The study was Prospective observational study. All the clinically suspected cases of Neonatal Sepsis admitted to the Neonatal word from January 2015 to December 2015 were included in the study. Clinically suspected cases of neonatal sepsis further evaluated with blood cultures and antibiotic susceptibility testing using the Kirby Bauer disc diffusion method. Data was collected for the following variables: Demographic profile, haematological profile, blood culture result and antibiotic sensitivity patterns.Results : Total 96 cases clinically suspected neonatal sepsis were included in the study. Among them 29 cases (30.21%) was culture positive septicemia. Klebsiella pneumoniae was the most common isolate accounting for 31.03% cases followed by Escherichia coli 27.59%. In Klebsiella infection most common sensitivity were Imipenum and Ciprofloxacin which were 77.78 and 33.33% respectively. In E.coli common sensitive drugs were Imipenum and Amikacin. In serratia common sensitive drugs were Imipenum, Netlmicin and Ciprofloxacin.Conclusion : K. pneumoniae was the most common pathogen. Most common sensitivity was Imipenum, Amikacin, Ciprofloxacin, Gentamicin, Netlmicin, and Ceftazidime,.Northern International Medical College Journal Vol.8(1) July 2016: 174-177